KEDUDUKAN SUMBANGAN PIHAK KETIGATERHADAP KEUANGAN DAERAH PROPINSI LAMPUNG - M, Yulia Netta (Lampung University)
local revenue source can be derived from local revenues, equalization funds, and other income. The position of third-party contributions to the area is a countrys financial in the sense of acceptance into the local treasury and included in the budget. The main factors supporting the implementation of third-party donation receipt to the area in Lampung is, the magnitude of the potential areas that could be explored as a source of local revenue, in addition to the number of companies that can be used as donors to contribute to the region.Â Keywords: SPK, Regional Finance